Home automation with energy efficiency system - Izet, Muhammad Hadif Nazrul; Azli, Shakira Azeehan; Nordin, Siti Aminah; Mohamad, Nurul Nadia (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
The Home Automation and Energy Efficiency System project is a prototype that aims to enhance household management by integrating renewable energy sources with Internet of Things (IoT) technology. The system automates and optimizes household utility control such as lighting, HVAC, and appliances using a microcontroller and a variety of sensors, including motion sensors, temperature and humidity sensors, and light sensors. The project shows considerable convenience and energy efficiency improvements, contributing to environmental sustainability. The IoT platform provides remote monitoring and control, allowing users to operate their home systems from anywhere via a smartphone application. This capability, together with real-time data processing and monitoring, ensures energy savings and user comfort by automatically controlling equipment based on occupancy and surroundings. The results of this project demonstrate its ability to reduce energy usage and promote sustainable living practices